Analisis Kinerja Bidan Pegawai Tidak Tetap di Kabupaten Ogan Komering Ulu - Rizki Intan Pratiwi; Chairil Zaman; Dewi Suryani (Jurnal Kesehatan Saelmakers PERDANA, 2022)
The health sector is a very important element in the human resource development strategy. One of the strategies is the existence of a temporary employee midwife placement policy (PTT). This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is no relationship between age (p = 1,000), marital status (p = 0.836), place of work (p = 0.865) with the performance of PTT midwives in Ogan Komering Ulu Regency in 2021. There is a relationship between supervision (p = 0.044; OR = 2.435), rewards (p = 0.000; OR = 3.407), facilities and infrastructure (p = 0.049; OR = 1.713), and superior support (p = 0.024; OR = 1.845) with the performance of PTT midwives in Ogan Komering Ulu Regency 2021. The most dominant variable is reward (p=0,000;OR=3,455). Suggestions for the OKU District Health Office, the findings of this study can be used by the health department, especially the Ogan Komering Ulu District in order to increase the rewards, supervision and support of superiors. So that the performance of the midwife will be good.